(untitled) (African Human Mobility Review, 2021)
The movement of people across national boundaries on the African continent, for the purposes of earning a living through gainful employment, engaging in cross-border trade or visiting their kin, is commonplace. However, the extent to which political power and authority permits this mobility is dependent on specific historical and political factors of each country. This paper traces and examines Ethiopian state presence at the Togochale border in the east of the country by examining patterns of cross-border movement – namely migration, refugee movement and cross-border trade – since the 1960s. Using archival sources and secondary sources, the paper constructs a historical narrative of strong state presence in this border area. Furthermore, the paper argues that the notable presence of the Ethiopian state at this border is a consequence of how the Ethiopian state conceptualises the notion of territorial statehood, which is shaped by the country’s history. Popular understandings suggest that local populations hold much sway in African border areas, rather than the central state, which is often confined to the capital – miles away from the border. Therefore, the presence of the Ethiopian state at the Togochale border appears to depart from the norm of limited state presence in African borderlands.